Early detection of the impact of combined taxane and carboplatin treatment on autonomic nerves in patients with cervical cancer: Measurement of heart rate variability - Liu, Jian; Guan, Weizheng; Sun, Yilin; Wang, Yuling; Li, Guangqiao; Zhang, Sai; Shi, Bo (Frontiers in Physiology, 2023)
Background: Previous studies have shown that heart rate variability (HRV) analysis is a sensitive indicator of chemotherapy-induced cardiotoxicity. However, most studies to date have observed long-term effects using long-term analyses. The main purpose of this study was to evaluate the acute effect of chemotherapy on the cardiac autonomic nervous system (ANS) in patients with cervical cancer (CC) by examining short-term HRV. Methods: Fifty patients with CC admitted to the Department of Gynecology and Oncology of the First Affiliated Hospital of Bengbu Medical College were enrolled in the study. Based on their chemotherapy regimens, the patients were divided into a DC group (docetaxel + carboplatin) and a TC group (paclitaxel + carboplatin). A 5-min resting electrocardiogram (ECG) was collected before and the day after chemotherapy: the time domain (standard deviation of normal-to-normal intervals (SDNN) and root mean square of successive differences (RMSSD)) and frequency domain (low-frequency power (LF), high-frequency power (HF), and (LF/HF)) parameters were analyzed, and the differences before and after chemotherapy were compared. Results: The results showed that SDNN, RMSSD and HF were significantly higher in the DC and TC groups after chemotherapy than before (p < 0.05, Cohen’s d > 0.5). In addition, LF was significantly higher after TC than before chemotherapy (p < 0.05, Cohen’s d > 0.3), and LF/HF was significantly lower after DC than before chemotherapy (p < 0.05, Cohen’s d > 0.5). Conclusion: Chemotherapy combining taxane and carboplatin can increase the HRV of CC patients in the short term, and HRV may be a sensitive tool for the early detection of chemotherapy-induced cardiac ANS perturbations.